Application of silver nanoparticle‐based SERS spectroscopy for DNA analysis in radiated nasopharyngeal carcinoma cells. (25th February 2013) - Ou, Lin; Chen, Yang; Su, Ying; Huang, Yangwen; Chen, Rong; Lei, Jinping
<x xml:space="preserve">Abstract</x> This work aims to explore the application of silver nanoparticle‐based surface‐enhanced Raman scattering (SERS) for nasopharyngeal carcinoma cell line CNE2's DNA analysis after X‐ray radiation. The cells are separated into control group and radiated groups with different dose of 6, 10, 15 and 20 Gy. The results show that after radiation (6, 10, 15 and 20 Gy), the DNA of radiated CNE2 have changed after 72 h of cell incubation. Principal components analysis is employed for significant differences and the DNA extracted after 72 h of incubation show significant divisions from control group. Moreover, a classifier based on support vector machines shows high classification accuracy between DNA extracted after 72 h of incubation and control group. In conclusion, this study first reveals SERS characteristics of CNE2's DNA under different dose of X‐ray radiation, and the final results may do favor to make known the mechanism of X‐ray radiation interacting with tumor. Copyright © 2013 John Wiley & Sons, Ltd.